Pengaruh Resiliensi Akademik Terhadap Stres Akademik Mahasiswa Pendidikan Bahasa Arab IAIN Syekh Nurjati Cirebon - Fitri Nurkholipah; Septi Gumiandari (Lembaga Pengembangan Kinerja Dosen, 2024)
Students are vulnerable to experiencing academic stress caused by the large workload and inability to adapt to lectures. If students cannot solve these problems efficiently, more serious problems will arise. This article aims to analyze and describe the resilience abilities of IAIN Syekh Nurjati Arabic Language Education study program students in dealing with academic stress. This research aims to 1) Analyze the Stress Resilience abilities of students in the IAIN Syekh Nurjati Cirebon Arabic Language Education study program 2) Analyze the academic stress that occurs in the IAIN Syekh Nurjati Cirebon Arabic Language Education study program 3) Describe the Influence of Stress Resilience in managing the Academic Stress experienced by Student of the Arabic Language Education Study Program at IAIN Syekh Nurjati Cirebon. research conducted on Arabic Language Education Students at UIN Siber Syekh Nurjati Cirebon, it can be concluded that there is an influence of Stress Resilience on Academic Stress experienced by students. Of the 10 students used as samples, 1 student had very high stress resilience, 4 students had high stress resilience, and 5 students had moderate resilience. This ability is seen from several aspects, including: 1) Self-Esteem ability (an individual's ability to assess things related to themselves) 2) Optimism ability 3) Ability to deal with stress 4) Moral ability. The Academic Stress experienced by students is indicated by 1) Physical aspects of stress such as students experiencing physical changes 2) Emotional aspects of stress such as students being emotionally disturbed 3) Mental aspects of stress such as students experiencing bad mental health 4) Behavioral aspects of stress such as students feeling excessive fear towards learning and students experience a decrease in learning motivation.